The Role of Green Human Resource Management: Analysis of Organizational Culture, Innovation and Leadership - Ryani Dhyan Parashakti; Wenny Desty Febrian; Achmad Tarmizi; Elyas Satria; Didin Hikmah Perkasa; Lingga Yuliana (Dinasti International Journal of Education Management And Social Science, 2024)
Literature review research on the role of green human resource management: Analysis of organizational culture, innovation and leadership is a scientific literature article in the scope of human resource management science. The purpose of this literature research is expected to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of human resource management. The approach used in this study is descriptive qualitative. The data collection technique is using literature studies or based on relevant previous research. The data used in this descriptive qualitative approach comes from previous research that is relevant to this study and is sourced from academic online media such as the Scopus Elsevier Journal, Emerald, Sage, WoS, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. The results of this literature review include: 1) Organizational Culture plays a role in green human resource management; 2) Innovation plays a role in green human resource management; and 3) Leadership plays a role in green human resource management.